Plant roots fuel tropical soil animal communities - Zhou, Zheng; Lu, Jing‐Zhong; Preiser, Jooris; Widyastuti, Rahayu; Scheu, Stefan; Potapov, Anton (Ecology letters, 2023)
Belowground life relies on plant litter, while its linkage to living roots had long been understudied, and remains unknown in the tropics. Here, we analysed the response of 30 soil animal groups to root trenching and litter removal in rainforest and plantations in Sumatra, and found that roots are similarly important to soil fauna as litter. Trenching effects were stronger in soil than in litter, with an overall decrease in animal abundance in rainforest by 42% and in plantations by 30%. Litter removal little affected animals in soil, but decreased the total abundance by 60% in rainforest and rubber plantations but not in oil palm plantations. Litter and root effects on animal group abundances were explained by body size or vertical distribution. Our study quantifies principle carbon pathways in soil food webs under tropical land use, providing the basis for mechanistic modelling and ecosystem‐friendly management of tropical soils. Our study quantifies the importance of litter vs. living root resources for soil animals across 30 taxonomic groups after conversion of rainforest into monoculture plantations. The results suggest that roots are of similar importance to litter for the soil animal food web, with root trenching effects being stronger in soil than in litter and litter removal little affecting animals in soil. Litter and root effects on animal abundances were related to animal body size or vertical distribution in soil and thus shape soil animal communities by different mechanisms.